Empirical approaches to the phonological structure of words - Ulbrich, Christiane; Werth, Alexander; Wiese, Richard (Linguistische Arbeiten ;, 2018)
One of the basic grammatical categories in linguistics is the phonological word. But how are words made up in terms of their sounds? And how is the information on the sound structure of words used in the processing of words? The multidimensionality of the phonological word relates it to semantics, morphology, phonology and syntax. It is nevertheless a category that has only been an object of serious study since the prosodic turn in phonology and thus cannot be considered an established category of grammatical description. This volume brings together scholars interested in the complex relations of the phonological word, applying different empirical approaches.